Combined effect of temporal inundation and aboveground-cutting on the growth performance of two emergent wetland plants, Phragmites australis and Bolboschoenus planiculmis - Park,Hee-Sun; Kim,Ji Yoon; Kim,Gu-Yeon; Jo,Hyunbin; Joo,Gea-Jae (PeerJ, 2024)
Background Phragmites australis is a common foundation species found in inland and brackish estuarine ecosystems. P. australis stands provide a wide range of habitats for wetland organisms and perform essential functions, such as nutrient cycling, pollutant filtration, wave energy reduction, and soil stabilization. However, excessive growth of P. australis can degrade the quality of wetland habitats, thereby reducing the functions of restored wetlands. Methods In this study, we investigated the effectiveness of vegetation management techniques, such as aboveground cutting and temporal inundation with varying depth and periodicity, in controlling the growth performance of P. australis and adjacent vegetation, Bolboschoenus planiculmis. Differences in growth responses to manipulated inundation stress between P. australis and B. planiculmis were measured. Results Inundation stress of 10–50 cm caused significantly greater inhibition of growth performance in B. planiculmis compared to P. australis. The combination of aboveground-cutting and inundation treatments resulted in a significant inhibitory effect on the growth performance and survival rate of P. australis. The growth performance of P. australis, including stem volume and biomass, decreased and its mortality rate increased. Our manipulated experiment suggests a combined treatment approach of moderate inundation, such as 5–10 cm for 20–30 days, and aboveground cutting to manage the overgrowth of P. australis in restored brackish wetlands.
Keywords: Brackish wetland; Food plant; Mesocosm experiment; Mortality; Vegetation management; Water level; Wetland restoration